Health equity funds as the pathway to universal coverage in Cambodia: care seeking and financial risk protection. Issue 1 (17th December 2020) - Jithitikulchai, Theepakorn; Feldhaus, Isabelle; Bauhoff, Sebastian; Nagpal, Somil
Abstract: Cambodia has developed the health equity fund (HEF) system to improve access to health services for the poor, and this strengthens the health system towards the universal health coverage goal. Given rising healthcare costs, Cambodia has introduced several innovations and accomplished considerable progress in improving access to health services and catastrophic health expenditures for the targeted population groups. Though this is improving in recent years, HEF households remain at the higher risk of catastrophic spending as measured by the higher share of HEF households with catastrophic health expenses being at 6.9% compared to the non-HEF households of 5.5% in 2017. Poverty targeting poses another challenge for the health system. Nevertheless, HEF appeared to be more significantly associated with decreased out-of-pocket expenditure per illness among those who sought care from public providers. Increasing population and cost coverages of the HEF and effectively attracting beneficiaries to the public sector will further enhance the financial protection and pave the pathway towards universal coverage. Our recommendations focus on leveraging the HEF experience for expanding coverage and increasing equitable access, as well as strengthening the quality of healthcare services.